O papel da taxa de filtração glomerular á admissão hospitalar na incidência e na mortalidade da lesão renal aguda associada ao infarto agudo do miocárdio - Bruetto, Rosana Gobi (2012)
The estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73m2 at admission is associated with increased risk of death after acute myocardial infarction (AMI). However, the role of admission eGFR on the incidence and mortality of acute kidney injury (AKI) after AMI has been poorly studied. The aim of this study is to investigate if impaired admission eGFR influences the incidence and mortality of AKI after AMI. A total of 1.012 consecutive AMI patients from a prospective database were analyzed and 828 subjects were included. The diagnostic criteria for AKI was a percent increase in serum creatinine (SCr) ≥ 50 % from baseline (RIFLE criteria) in the first seven days of hospitalization. Patients were divided into four subgroups: admission eGFR ≥ 60 mL/min/1.73m2 and no AKI (reference), admission eGFR < 60 mL/min/1.73m2 and no AKI, admission eGFR ≥ 60 mL/min/1.73m2 and AKI, admission eGFR < 60 mL/min/1.73m2 and AKI. Impaired eGFR had no impact in the incidence of AKI. On the other hand, impaired admission eGFR had a striking influence on the mortality of AMI associated with AKI. In Cox multivariate analysis, 30 days mortality was significantly higher for eGFR < 60 mL/min/1.73m2 and no AKI (adjusted hazard ratio [AHR] 2.00, p=0.020), for eGFR ≥ 60 mL/min/1.73m2 and AKI (AHR 4.76, p < 0.001) and for eGFR < 60 mL/min/1.73m2 and AKI (AHR 6.27, p < 0.001) compared to patients with eGFR ≥ 60 mL/min/1.73m2 who did not develop AKI. One year mortality was significantly higher only for eGFR < 60 mL/min/1.73m2 and who developed AKI (AHR 3.05; p=0.002) compared with patients with eGFR ≥ 60 mL/min/1.73m2 without AKI. In conclusion, overlap of low admission eGFR and AKI development was associated with the worst early prognosis after AMI. Remarkably, the long term mortality rate in patients who developed AKI, was only increased in the group with an impaired admission eGFR.